2018
DOI: 10.1016/j.jallcom.2017.12.262
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical and experimental investigation of Eu-doped ZnO nanorods and its application on dye sensitized solar cells

Abstract: a b s t r a c tThis paper describes the electrodeposition of Europium-doped Zinc Oxide (ZnO) nanorods as well its application as photoanodes in dye sensitized solar cells (DSSCs). The incorporation of the Europium in the ZnO structure was evidenced by X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). The DSSCs based on Eu-doped nanorods photoanodes exhibits a higher conversion efficiency value (h) (0.50%) compared to the undoped photoanodes (0.34%). Mott-Schottky analysis was performed and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 58 publications
6
24
0
Order By: Relevance
“…In the DSSCs, particularly, the mesoporous metal oxide mainly the basis of TiO 2 with PEC < 8% (Sharma et al, 2017). However, many other oxides may also be used for applications in DSSCs are integrated into devices anchored to the dye is placed between two glass conductive plates in the presence of an electrolyte, which is generally a redox system (Polman et al, 2016;Sharma et al, 2017;da Fonseca et al, 2018). Fundamentally, by drawing attention to DSSC application, when dye molecules (also known as photosensitizers) capture the photons of sunlight.…”
Section: Eletrochemical Potencial Usementioning
confidence: 99%
See 1 more Smart Citation
“…In the DSSCs, particularly, the mesoporous metal oxide mainly the basis of TiO 2 with PEC < 8% (Sharma et al, 2017). However, many other oxides may also be used for applications in DSSCs are integrated into devices anchored to the dye is placed between two glass conductive plates in the presence of an electrolyte, which is generally a redox system (Polman et al, 2016;Sharma et al, 2017;da Fonseca et al, 2018). Fundamentally, by drawing attention to DSSC application, when dye molecules (also known as photosensitizers) capture the photons of sunlight.…”
Section: Eletrochemical Potencial Usementioning
confidence: 99%
“…Fundamentally, by drawing attention to DSSC application, when dye molecules (also known as photosensitizers) capture the photons of sunlight. Consequently, the photoelectrons move directly from the LUMO (lowest unoccupied molecular orbital), which is the excited state of the dye (a liquid redox electrolyte, usually I − /I 3− non-aqueous solution), to the CB of the semiconductor material as electron selective contact and therefore diffuse to the electrode conductor (da Fonseca et al, 2018;Nunes et al, 2018). Hence, the ionized dye molecules are, in turn, reduced by the reducible oxide charge on the electrolyte.…”
Section: Eletrochemical Potencial Usementioning
confidence: 99%
“…It is well known that properties of materials at nano-scale are markedly dependent on their size, shape or morphology; thus, the control of features such as porosity, surface area or specific orientation has attracted much interest for improving the performance of ZnO-based devices [5]. In this respect, ZnO morphology is highly versatile as it encompasses nanorods, nanowires, nanotubes, nanowalls, nanocups nanobelts, nanorings, nanosprings, nanobowls, nanoflowers, nanohelices and nanoparticles [1,[6][7][8]. For example, Wang et al reported a novel and improved ethanol gas sensor based on electrodeposited flower-like ZnO microstructures [9], Psychoyios et al fabricated a ZnO-based potentiometric cholesterol biosensor with improved adsorption capability by improving the surface successfully applied to control the structure and orientation of ZnO electrodeposited nanostructures towards improving its performance in varying fields.…”
Section: Introductionmentioning
confidence: 99%
“…This higher activity can be explained by the following hypothesis: ZnO calcination allows the formation of a material with a low content of impurities, which favors the electronic transitions in the generation of radicals that degrade the dye and the drug. 19 The ZnO synthesized presented a catalytic activity superior to 60% of degradation, due to its crystalline size estimated at 21.1 nm, which gives it greater contact area. It was possible to observe the ZnO phase according to XRD and XPS; and the tendency of nanotubes formation in SEM images, that gives the material a greater efficiency of the process of degradation of the pollutant solution, since there is no significant intervention of other species.…”
Section: Photocatalytic Activity Of the Materialsmentioning
confidence: 97%
“…The energy of separation between the peaks was 23 eV according to the literature. 19 Figure 3b shows the XPS spectrum of the O1s region deconvolved in two Gaussian curves indicating the presence of two chemical species around the oxygen atom. Two Gaussian curves labeled as (Zn-OH) and (Zn-O) were used to adjust the experimental data.…”
Section: Characterization Of Synthesized Znomentioning
confidence: 99%